Functional analysis of the sialic acid-binding adhesin SfaS of pathogenic Escherichia coli by site-specific mutagenesis. - Morschhäuser, J (1990)
The gene coding for the sialic acid-specific adhesin SfaS produced by the S fimbrial adhesin (sfa) determinant of Escherichia coli has been modified by oligonucleotide-directed, site-specific mutagenesis. Lysine 116, arginine 118, and lysine 122 were replaced by threonine, serine, and threonine, respectively. The mutagenized gene clusters were able to produce S fimbrial adhesin complexes consisting of the S-specific subunit proteins including the adhesin SfaS. The mutant clones were further characterized by hemagglutination and by enzyme-linked immunoassay tests with antifimbria- and anti-adhesin-specific monoclonal antibodies, one of which is able to block S-specific binding (Moch et al., Proc. Natl. Acad. Sci. USA 84:3462-3466, 1987). The lysine-122 mutant clone was indistinguishable from the wild-type clone in these assays. Replacement of lysine 116 and arginine 118, however, abolished hemagglutination and resulted in clones which showed a weak (lysine 116) or a negative (arginine 118) reaction with the antiadhesin-specific antibody A1. We therefore suggest that lysine 116 and arginine 118 have an influence on binding of SfaS to the sialic acid residue of the receptor molecule. Substitution of arginine 118 by serine also had a negative effect on the amount of SfaS adhesin proteins isolated from the S fimbrial adhesin complex.